2005
DOI: 10.1590/s1413-81232005000100006
|View full text |Cite
|
Sign up to set email alerts
|

Homens e saúde: diversos sentidos em campo

Abstract: Para mim é uma grande satisfação a oportunidade de participar deste debate que considero tão importante. Além da pertinência do tema que já valeria a empreitada, o artigo "Homens e saúde na pauta da Saúde Coletiva" consegue mapear diversas dimensões de um mesmo campo. Se por um lado essa amplitude deixa o debatedor com vontade de referir várias questões ao mesmo tempo -o que é aqui impossível; por outro, oferece ao leitor uma oportunidade ím-par de reflexão pelo que parabenizo os autores.Também gostaria de sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
3
0
7
Order By: Relevance
“…Despite a certain consensus that there seems to be a historic and cultural character in the category of gender (Nascimento, 2005), when speaking of masculinities and femininities this accord does not seem to be so evident.…”
Section: Refining the Concept: Understanding Masculinitiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite a certain consensus that there seems to be a historic and cultural character in the category of gender (Nascimento, 2005), when speaking of masculinities and femininities this accord does not seem to be so evident.…”
Section: Refining the Concept: Understanding Masculinitiesmentioning
confidence: 96%
“…Looking at the collective health/public health literature, it was confirmed that men's access to, or better yet, difficulty in accessing health services is a relevant concern (Schraiber et al, 2010;Couto et al, 2010;Toneli et al, 2010;Pinheiro and Couto, 2008;Nascimento and Gomes, 2008;Gomes et al, 2007;Paschoalick et al, 2006;Araújo and Leitão, 2005), and this is one of PNAISH's main objectives. Schraiber et al (2010) stress that Atenção Primária a Saúde (Primary Care: APS) -the main access point to health services -is markedly aimed at women's health problems, as prevention and health care are socially characterized as essentially female tasks.…”
Section: Men's Health and Masculinitiesmentioning
confidence: 99%
“…Isso implica também investigar como estão sendo significadas no universo feminino. Esta premissa inclui a clareza de como os serviços de saúde, de uma forma geral, acabam por refletir a organização social com base no gênero (NASCIMENTO, 2005), antes de afirmarmos que os homens se excluem ou foram excluídos das esferas de cuidado de si e dos outros.…”
Section: Considerações Finaisunclassified
“…1 Esta meta teve seu pontapé inicial em agosto deste ano, com o lançamento da Política Nacional de Atenção Integral à Saúde do Homem (PNAISH). Isto reflete a amplitude da temática de homens e serviços, que vem sendo alvo de atenção de pesquisadores/as das mais diversas áreas do Brasil e América Latina (GIFFIN, 2005;ARILHA, 1998;TONELI, 2000;NASCIMENTO, 2005;SCHRAIBER;COUTO, 2005). O interesse na América Latina e Caribe por experiências de trabalho com homens, em sexualidade e saúde reprodutiva, vem crescendo nos últimos anos, sobretudo a partir de demandas que têm origem em ações desenvolvidas com mulheres, em diferentes campos (LYRA; MEDRADO, 2005).…”
unclassified
“…8 It crystallizes socially constructed oppositions as if they were data from nature: it discourages men to seek health services and sees women as caregivers and essentially the only responsible for the sphere of health. 15 It is possible to observe different attitudes in relation to health: healing practices for men and preventive practices by women. Although there has been a progressive accumulation of reflections within health promotion under a gender perspective, the care for themselves, in terms of health, and also the care of others are still missing from the process of socialization of men.…”
Section: Resultsmentioning
confidence: 99%